On the verge of convergence : social stratification in Eastern Europe - Domański, Henryk (New York : Central European University Press, 2000)
"Based upon comparative surveys and newly obtained data, Domanski's book provides a major contribution to the study of social transformation in Central and Eastern Europe after 1989. Focusing on Bulgaria, the Czech Republic, Hungary, Poland, Russia and Slovakia, the author provides substantial comparative information relating to social structure, mobility, inequality, lifestyle and economic stratification." "Applying the Erikson-Goldthorpe classification of class positions, Domanski presents fully comparable data to enable political comparisons to be made with other countries, especially those with firmly established free-market economies."--Jacket
Includes bibliographical references (pages 173-181) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Social classes -- Europe, Eastern; Social structure -- Europe, Eastern; Europe, Eastern -- Social conditions -- 1989-; Europe, Eastern -- Economic conditions -- 1989-; Post-communism -- Europe, Eastern; Classes sociales -- Europe de l'Est.; Structure sociale -- Europe de l'Est.; Postcommunisme -- Europe de l'Est.; Europe de l'Est -- Conditions sociales -- 1989-; Europe de l'Est -- Conditions économiques -- 1989-; SOCIAL SCIENCE -- Social Classes; Economic history; Post-communism; Social classes; Social conditions; Social structure; Eastern Europe; Sociale stratificatie; Sociale verandering; Since 1989